2018
DOI: 10.1002/jcla.22384
|View full text |Cite
|
Sign up to set email alerts
|

Test‐1 analyzer and conventional Westergren method for erythrocyte sedimentation rate: A comparative study between two laboratories

Abstract: The study showed that the role of the hospital and the capacity of testing are important in choosing the instrument for measuring ESR. Furthermore, the patient profile, especially malignancy possibility and Hct level, may be important for instrument selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Sonmez et al also found a poor correlation between the two methods at high ESR values ( p > 0.10). 9 Dhruva et al also had similar observations in patients with HCT between 30 to 35%. They realized that samples with high ESR values vary considerably around the mean difference compared with samples which had normal ESR readings.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Sonmez et al also found a poor correlation between the two methods at high ESR values ( p > 0.10). 9 Dhruva et al also had similar observations in patients with HCT between 30 to 35%. They realized that samples with high ESR values vary considerably around the mean difference compared with samples which had normal ESR readings.…”
Section: Discussionmentioning
confidence: 60%
“…Sonmez et al and Romero et al, similar to our study, evaluated the effect of low HCT (< 35%) on ESR levels. Sonmez et al 9 used samples of 755 patients and divided the corrected ESR values into low (≤20 mm/hour) and high (> 20 mm/hour) range and according to HCT (≥35%, < 35%) levels. Like our study, Sonmez et al 9 also found that in anemic patients, ESR values measured by the direct Westergren method were higher than automated method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The control blood sample ESR was 6 mm/h and CQDs‐treated blood sample was 7.5 mm/h. The normal range of ESR by Westergren method is 15 mm/h . The obtained ESR value in CQDs‐treated (test) blood sample was within the acceptable range.…”
Section: Resultsmentioning
confidence: 57%